Effects of Different Surface Treatments and Accelerated Aging on Dental Zirconia—An In Vitro Study - Mihaela Pantea; Lucian Toma Ciocan; Vlad Gabriel Vasilescu; Georgeta Voicu; Adrian-Ionut Nicoară; Florin Miculescu; Robert Ciocoiu; Ana Maria Cristina Țâncu; Elena Georgiana Banu; Marina Imre (Journal of Functional Biomaterials)
This in vitro study aimed to compare the effects of various surface treatments and hydrothermal aging on the phase composition, microstructure, and compressive strength of dental zirconia (ZrO2). Forty-eight zirconia cubes (8 × 8 × 8 mm) were fabricated using CAD/CAM from two materials: infrastructure zirconia (Group S1) and super-translucent multilayered monolithic zirconia (Group S2). Four samples of each material were analyzed in their pre-sintered state (S1-0, S2-0). The remaining specimens were sintered and assigned to sub-groups based on surface treatment: untreated, sandblasted with 30 µm or 50 µm Al2O3, polished, or polished and glazed. Characterization was performed using EDX, SEM, XRD with Rietveld refinement, Raman spectroscopy, and compressive testing before and after accelerated hydrothermal aging, according to EN ISO 13356:2015. EDX revealed a higher yttria content in monolithic zirconia (10.57 wt%) than in infrastructure zirconia (6.51 wt%). SEM images showed minimal changes in polished samples but clear surface damage after sandblasting, which was more pronounced with larger abrasive particles. XRD and Raman confirmed that sandblasting promoted the tetragonal (t-ZrO2) to monoclinic (m-ZrO2) phase transformation (t→m), amplified further by hydrothermal aging. The polished groups showed greater phase stability post-aging. Compressive strength decreased in all treated and aged samples, with monolithic zirconia being more affected. Polished samples displayed the best surface quality and structural resilience across both materials. These findings underline the impact of clinical surface treatments on zirconia’s long-term mechanical and structural behavior.